Manifestations, self-confidence, comparisons, and perfectionistic aspirations before orthognathic surgery - Makauskienė, Ilona (Psichologija, 2012)
Interest in the psychological factors involved in malocclusion appeared thirty years ago. The most frequent aspect of research is self-evaluation. However, up to date, there are no empiric half-structured interview investigations with subjects of this group, in which manifestations of confidence, comparison, and perfectionistic aspirations would be explored wider and in more detail. No studies with orthognathic subjects were conducted in Lithuania, so we hope the data of our research will help to fill this gap. Seventy-three subjects with some kind of malocclusion were involved. The research lasted from 2006 to 2010. Self-representations were investigated by means of a half-structured interview based on self-in-relation theory. Self-representations of the past, presents and future were explored, three significant others (mother, father, and best friend) were distinguished. A qualitative analysis of self-representations was conducted, and six categories were singled out. Self- representations of comparison were estimated considering the ideal and standards of the self, peer, father, mother, or partner. The assessments were divided into positive and negative. The subjects were grouped and compared according to parents’ relationship experience, age group, education, taunting experience.The data suggest that in subjects just before the surgery statistically significant changes occurred according to taunting experience; positive comparison representations diminished, more of statistically significant differences between the standpoints of mother and father self-representations showed up, unconfident representations increased. Based on the research results, we can predicate that the biggest risk pre-operative group comprised subjects with taunting experience and subjects with the experience of violence in the family, as these subjects expressed most negative self-representations of distrust and comparison. These subjects expressed statistically significantly more adolescent and actual distrust in mother representations. Comparison of data according to subjects’ age has revealed that subjects of the oldest group most of all seek to meet health, appearance, and profession perfectionist standards. Subjects of the youngest group most often compare themselves with standards of peers and father. Subjects aged 26–30 years after the surgery statistically significantly expect to be more satisfies with one’s own appearance. While comparing subjects according to education, appearance, self-representations of knowledge, and comprehension diverged. Self- representations of confidence/distrust and perfectionistic aspirations were most expressed in adolescent and actual time spans, while manifestations of comparison were expressed in all life spans.
Keywords: malocclusion; face attractiveness; self-confidence; self-comparison; orthognathic surgery